[Letter to the Tobacco Institute] (Tufts Archival Research Center, 2007)
Confidential; Letter from Susan Stuntz to Terry Frakes, regional director of the Tobacco Institute, regarding labor-industry cooperation on public smoking and cigarette excise taxes. Lists the unions that have participated in pro-industry events including testifying, media appearances and submitting statements.